1998
DOI: 10.1051/gse:19980504
|View full text |Cite
|
Sign up to set email alerts
|

Selection for reduced muscle glycolytic potential in Large White pigs I. Direct responses

Abstract: A six-generation selection experiment comprising a selected (S) and a control (C) line has been conducted with the objective of decreasing muscle glycolytic potential in purebred French Large White pigs. Both lines consisted of six to eight sires and about 40 dams per generation, and each dam produced two litters. The selection criterion in the line S was the in vivo glycolytic potential (IVGP) of the Longissimus (ld) muscle, measured on a shot-biopsy sample removed at 75 kg live weight on boars and gilts from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Correlations between GP and EBVs for daily gain and feed : gain ratio were weak and not significant, confirming previous results obtained in a French Large White population free from the RN ‐ allele (Le Roy et al. 1998).…”
Section: Resultssupporting
confidence: 88%
“…Correlations between GP and EBVs for daily gain and feed : gain ratio were weak and not significant, confirming previous results obtained in a French Large White population free from the RN ‐ allele (Le Roy et al. 1998).…”
Section: Resultssupporting
confidence: 88%
“…However, Femandez et al (1992) reported that lactate content in longissimus biopsy samples taken from the live animal was low, indicating that glycogenolysis occurred to a limited extent prior to sampling and during storage. Although a number of studies have measured glycolytic potential in muscle samples obtained from the live animal (Fernandez et al 1992;Estrade et al 1993;LeRoy et al 1998;Larzul el al. 1999), there is limited information on the impact of animal handling procedures before and during sampling and of the effect of sample preparation and storage prior to assay on GP values.…”
Section: Introductionmentioning
confidence: 99%